Art of Learning – An Art-Based Intervention Aimed at Improving Children’s Executive Functions - Andersen, Per Normann; Klausen, Marita Eggen; Skogli, Erik Winther (Frontiers in Psychology, 2019)
Executive functions (EF) can be conceptualized as a mean of behavioral self–regulation, and difficulties with EF may adversely affect school success, social function, cognitive and psychological development. Research about EF and how they are affected by various educational and psychosocial factors is sparse. EF are of great importance to understand how children can handle the challenges that they meet at various stages of development. There has been an increased focus on programs aimed at improving EF, either as a primary outcome, or as a supplemental result of a specific activity. In this randomized controlled study, 66 children (31 girls, mean age 7:1 yrs) were given an arts and culture rich intervention (Art of Learning) aimed at improving EF. EF were assessed with the Behavior Rating Inventory of Executive Functioning – teacher version (BRIEF-teacher form) before, immediately after, and six months after intervention. Outcome in the intervention group was compared to children from two schools serving as controls (n=37, 18 girls, mean age 7:3 yrs.). In addition, teachers from intervention schools were also interviewed both individually and in focus groups. The results reveal that both groups improved their EF, as measured with BRIEF, over time on the global executive composite score (GEC), the metacognition index (MI) and on behavioral regulation index (BRI). However, the intervention group displayed a significantly greater improvement than the control group on GEC and BRI. The teacher interviews reveal positive effects for the children when it comes to several aspects: collaboration, conflict management, inclusion, vocabulary and confidence. These factors are regarded as important for EF development and academic outcome. The results support the notion of best training transfer effects for tasks addressing global executive functioning and specifically behavioral regulation skills (BRI).